Furnace-03 Performance Efficiency at the Cepu Oil and Gas PPSDM Refinery Unit: Furnace-03 Performance Efficiency at the Cepu Oil and Gas PPSDM Refinery Unit - Indah Dhamayanthie; Dian Farkhatus Solikha; Istiqlaly Khaerunnisa; Nayif Muhamad Rizky (Jurnal Migasian, 2025)
Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas (PPSDM Migas) is a training and education institution located at Jalan Sorogo No. 1, Karangboyo Village, Cepu District, Blora Regency, Central Java Province. This research was carried out on November 01-30, 2023 at the PPSDM Migas Cepu Refinery Unit which focuses on heating equipment, namely the Furnace. Furnace is an advanced heating device in the refinery unit to heat crude oil with an output temperature of 330 - 350°C. The purpose this research is to calculate the variables that support the calculation of Furnace performance efficiency, calculate and know the efficiency value of Furnace-03, and know the things that affect the efficiency of furnace performance. Supporting variables in the calculation of Furnace efficiency in the form of Specific Gravity, 60 ° F Density, °API, and K-UOP values, the results obtained for Fuel Oil are 0.891, 890.294 kg/m3, 27.278, and 11.884, respectively. Whereas the values for Crude Oil are 0.839, 837.934 kg/m3, 37.217, and 12.048, respectively. The results of the calculation of the efficiency of Furnace-03 were obtained at 57.37% so that Furnace-03 was not suitable for operation. Where to achieve good efficiency the things that need to be considered are parameters, such as temperature and flow, as well as the age of the equipment.